Ide Peluang Usaha Analisis Bisnis dan Studi Kelayakan Bisnis - Siregar, Aditya; Putri, Lilis Agustina; Nabil, M. Devent (Universitas Serambi Mekkah, 2024)
The importance of business analysis and feasibility studies in business development. The success of a business is greatly influenced by proper financial planning, including cash flow analysis and risk assessment. This study uses a literature review method to evaluate various sources of information on entrepreneurship and the factors that influence business success. The research findings show that creativity in generating business ideas that are in line with market needs is essential to creating sustainable business opportunities.